AutoCad 2006 Instructor - A. Leach James (Mcgraw Hill, 2006)
AutoCAD is the market leader for all CAD software and is used by nearly two million students and professionals in architecture, engineering, construction, and design. Leach's AutoCAD 2006 Instructor is designed to teach AutoCAD 2006 for instructor-lead and independent study, providing complete coverage of the features and capabilities of AutoCAD.